General lack of use of placebo in prophylactic, randomised, controlled trials in adult migraine. A systematic review. (September 2016) - Hougaard, Anders; Tfelt-Hansen, Peer
Background: The Clinical Trials Subcommittee of the International Headache Society (IHS) recommends that a placebo arm is included in comparative randomised clinical trials (RCTs) of multiple prophylactic drugs due to the highly variable placebo response in migraine prophylaxis studies. The use of placebo control in such trials has not been systematically assessed. Methods: We performed a systematic review of all comparative RCTs of prophylactic drug treatment of migraine published in English from 2002 to 2014. PubMed was searched using the Cochrane Highly Sensitive Search Strategy for identifying reports of RCTs. Results: A placebo arm was used in <10% (three of 31) of prophylactic RCTs in migraine. In only 7.1% (two of 28) of the comparative RCTs without placebo was one drug superior to another drug. Thus in 26 RCTs, including one study requiring more than 75, 000 patient days, no difference was identified across treatment arms and conclusions regarding drug superiority could not be drawn. Conclusions: The majority of comparative, prophylactic migraine RCTs do not include a placebo arm. Failure to include a placebo arm may result in failure to demonstrate efficacy of potentially effective migraine-prophylactic agents. In order to benefit current and future patients, the current strong tendency to omit placebo-controls in these RCTs should be replaced by adherence to the guidelines of the IHS.